An Exploratory Study on the Challenges Encountered and Strategies Employed by the Philippine Child Caring Agencies Amidst COVID-19: Social Work Administration in the New Normal - Sina-on, Glennie Marie; Cometa-Lamberte, Hazel; Camba-Jontarciego, Diadem Rose (Indonesian Social Work Consortium (ISWC), 2022)
This paper presents the experiences of Child Caring Agencies (CCAs) in the Philippines that offer free residential care services for Children in Need of Special Protection (CNSP) amidst the COVID-19 pandemic. It discusses the challenges encountered and strategies employed in managing and operating the residential care facilities for children. The results show implications for the conduct of social work administration and the delivery of social welfare and services in residential settings.